Takhrij and Syarah Hadith of Agrotechnology Benefits of Ajwa Dates - Maulana Malik Muharramsyah; Wahyudin Darmalaksana; Agung Rahmadi (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss the Prophet's hadith about the benefits of Ajwa dates. This research method is qualitative through the takhrij and sharah hadith approaches with agrotechnological analysis. The results and discussion of this study are the benefits of Ajwa dates according to scientific research. The conclusion of this research is that the Prophet's hadith and syarah about the ajwa palm plant with agrotechnological analysis have many benefits, especially in the health sector.